To study the prevalence of insulin resistance in non-diabetes hypertensive subjects - Mohan, Gurinder; Kaur, Ranjeet; Nayyar, Gursimran Singh; Singh, Parminder (International Journal of Advances in Medicine, 2017)
Background: Hypertension is an important medical and public health problem in both developed and developing countries. It is an important risk factor for morbidity and mortality from coronary heart disease, stroke and renal disease. It is well recognized that hypertension coexists in varying degrees with conditions of obesity, insulin resistance/hyperinsulinemia and dyslipidemia, the interrelated metabolic disorders characteristic of metabolic syndrome. Methods: The study was carried out at Sri Guru Ram Das hospital, Amritsar, Punjab, India. A total of 150 patients were taken, out of which 75 were hypertensive and 75 healthy subjects more than 18 years of age were recruited. Serum insulin concentration was measured using a solid phase enzyme linked immunoassay based on the sandwich principle. Insulin resistance was determined by HOMA-IR (homeostasis model assessment of insulin resistance). Results: Statistically, the mean fasting serum insulin level was 17.09±8.17 μIu/ml in cases and 9.33±2.67μIU/ml in controls (reference range 2-25 μIU/ml); the difference was statistically significant (P <0.001). The mean value of HOMA-IR in cases was 3.86±1.84 as compared with controls with mean HOMA -IR value of 2.01±0.62. This difference was statistically significant (P <0.001). Conclusions: Essential hypertension is significantly associated with higher mean fasting insulin levels and insulin resistance. Hyperinsulinemia has a possible role in the pathophysiology of essential hypertension with insulin resistance being the likely predominant mechanism.